PENGARUH MEDIA INTERAKTIF ANIMASI TERHADAP MINAT BELAJAR PADA MATA PELAJARAN IPA SISWA KELAS IV SD NEGERI - adiansyah, rizki (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU, 2023)
This research aims to determine the influence of animated interactive media on interest in learning in science subjects for fourth grade students at public elementary schools. This type of research uses quantitative research and uses a quasi-experimental approach, or experimental design which is almost always used. The population is all individuals who are the source of sampling. So this population is the entire fourth grade of elementary school, totaling 46 people. The sample in this research was 46 people consisting of 23 control classes (class IVA) and 23 experimental classes (class IV B). In statistical analysis, the comparison between two groups can be evaluated by calculating the tcount value and comparing it with the ttable value. In this case, there are two groups that are compared based on the posttest and pretest. The tcount value for the posttest is 5.225, while the ttable value is 1.668. The decision that can be taken is that the null hypothesis (H0) for the posttest is rejected because the tcount value exceeds the ttable value. This means that there was a significant difference between the two groups when the posttest was carried out. The results of the pretest analysis show that the tcount value is 5.326, while the ttable value is 5.023. In this case, the decision taken is to accept the null hypothesis (H0) because the tcount value does not exceed the ttable value. Therefore, it can be concluded that there was no significant difference between the two groups when the pretest was carried out.